Mechanochromic, Shape‐Programmable and Self‐Healable Cholesteric Liquid Crystal Elastomers Enabled by Dynamic Covalent Boronic Ester Bonds - Ma, Jiazhe; Yang, Yanzhao; Valenzuela, Cristian; Zhang, Xuan; Wang, Ling; Feng, Wei (Angewandte Chemie International Edition, 2022)
Endowing a cholesteric liquid crystal elastomer (CLCE) exhibiting a helicoidal nanostructure with dynamically tailorable functionalities is of paramount significance for its emerging applications in diverse fields such as adaptive optics and soft robotics. Here, a mechanochromic, shape‐programmable and self‐healable CLCE is judiciously designed and synthesized through integrating dynamic covalent boronic ester bonds into the main‐chain CLCE polymer network. The circularly polarized reflection of CLCEs can be reversibly and dynamically tuned across the entire visible spectrum by mechanical stretching. Thanks to the introduction of dynamic boronic ester bonds, the CLCEs were found to show robust reprogrammable and self‐healing capabilities. The research disclosed herein can provide new insights into the development of 4D (color and 3D shape) programmable photonic actuators towards bioinspired camouflage, adaptive optical systems, and next‐generation intelligent machines. Cholesteric liquid crystal elastomers (CLCEs) exhibiting mechanochromic, shape‐programmable and self‐healable properties were synthesized by introducing dynamic covalent boronic ester bonds into the main‐chain CLCE polymer networks. This research shines new light onto the development of dynamic covalent polymers for emerging applications in areas of bioinspired camouflage, adaptive optics and smart soft robotics.